An assessment of private woodlot at Kaligonj upazilla of Jhenaidah district, Bangladesh: Socio-economic benefits of private woodlot (Bangladesh Journal of Agriculture, 2023)
The study presents an assessment of the species selection, management technique, and socio-economic benefits of raising private woodlot plantations in Kaligonja upazila, Jhenaidah district of Bangladesh during 2016-2017. A total of 80 woodlot owners were surveyed randomly to assess the status of woodlot plantations. Major growers (55%) were middle-aged (41-55 years) and dominated by males (95%). About 90% of woodlots were rectangular in size and monoculture in species composition (70%) of which about 75% was Swietenia macrophylla. A total of 77.5% of owners has single ownership, whereas about 97.5% of the respondents practice woodlot on their landowner. The majority of the land (85%) was previously used as agricultural landowner. The socioeconomic benefit was timber production, utilization of fallow land, income generation, fuel wood production, etc. The owners manage their woodlots by following traditional and silvicultural techniques. Most of the respondents are conscious and have general knowledge of thinning (80%) and pruning (97.5%). Selection felling systems (60%) and clear felling (40%) were the two types of harvesting systems found in this area. About 90% of respondents fixed the rotation period ranging from 10 to 20 years depending on the species and market value. They still need proper guidance and training to increase their knowledge and efficiency for the maximum productivity of woodlots in the study area.Bangladesh J. Agri. 2023, 48(1): 67-80